Enhancing the Indonesia Air Defense System: Confronting the challenges and military build-up In the Indo Pacific region - Joesoef, Norman (Technium Social Sciences Journal, 2022)
As the fourth most populous country in the world, and the 17th strongest military power in the world (according to global fire power index) Indonesia is racing towards modernisation of its militaries. Understanding the worldwide conflict of the 21st century against the backdrop of South China Sea potential conflict, and as a non-bloc country, Indonesia is at a crossroads. Between reality and survivability. Modern Air Defence Systems is the key to national sovereignty and safety.